Landscape Evaluation of Color-leaf forest from the Perspective of Different Scales: A Case of Jinyang Village in China. Issue 3 (February 2020) - Lu, C T; Jiang, D; Huang, M; Wen, Q; Liu, X
Abstract: With the development of forest tourism, Color-leaf forest has gradually become one of the most popular tourism destination. Based on related researches about forest landscape evaluation, this paper takes Jinyang village as the research object, which is known as the "Western Ginkgo No. 1 Village", to conduct scenic beauty evaluation (SBE) on different scales of the same landscape. The result shows that the landscape outside the forest is affected by terrain changes, overall landscape combination, landscape contrast, human landscape, and human activities; the landscape inside the forest is affected by diameter, color of the leaves, composition and density of the forest, and leaf coverage. The results will provide some references for the practice of forest landscape planning in China.